Ultrahigh-fluidity LCP (Liquid Crystal Polymer) composite material and preparation method thereof
By adopting specific formulation and process conditions in LCP composites, including the use of modifiers and nanoscale mica powder, the problem of poor fluidity of LCP materials is solved, significantly improving its fluidity and processing properties while maintaining good mechanical properties.
Patent Information
- Application Number
- CN202411461308.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-03-11
AI Technical Summary
The high viscosity and poor fluidity of LCP materials lead to the resistance of the melt flow when forming thin and small products during the injection molding process, which can easily lead to poor flow, lack of glue and dissatisfied filling, affecting product quality.
The formulation of an ultra-high fluidity LCP composite material, including LCP resin, polyethylene terephthalate, polyethylene, nano-scale mica powder, modifier and polypropylene powder, is obtained by blending N,N-ethylene bisstearic acid amide, polyvinyl alcohol and silicone masterbatches, optimize the proportion and process conditions of each raw material, significantly reduce the viscosity of LCP, and improve its fluidity.
The viscosity of LCP composite material is significantly reduced, and its fluidity is improved, making it easier to fill the mold during processing to form ultra-thin products with uniform structures, while maintaining high strength, high modulus, wear resistance, heat resistance, weather resistance and electrical properties.
Smart Images

Figure BDA0005091942430000051 
Figure BDA0005091942430000061 
Figure BDA0005091942430000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of LCP processing technology, and more specifically, to an ultra-high fluidity LCP composite material and a preparation method thereof. Background Art
[0002] Liquid crystal polymer resin (LCP) is a material with high strength, high modulus, wear resistance, heat resistance, weather resistance and electrical properties, and is widely used in the fields of electronics, communications, aerospace, automobiles and medical technology. With the development of science and technology, most of the parts required in the fields of electronics, communications, aerospace, automobiles and medical technology are developing towards smaller size and thinner thickness, and correspondingly, LCP products are also developing towards smaller size and thinner thickness.
[0003] In the actual production process, it is found that LCP has high viscosity and poor fluidity. During the injection molding process to form thin and small products, the melt encounters greater resistance when flowing, which can easily lead to poor flow, glue shortage and filling dissatisfaction, affecting the quality of LCP products. Summary of the invention
[0004] In order to solve the problem of high viscosity and poor fluidity of liquid crystal polymer resin, the present application provides an ultra-high fluidity LCP composite material and a preparation method thereof.
[0005] In a first aspect, the present application provides an ultra-high fluidity LCP composite material, which adopts the following technical solution: an ultra-high fluidity LCP composite material, prepared from the following raw materials in weight percentage: LCP resin 40-50% Polyethylene terephthalate 10-15% Polyethylene 9-13% Nano-grade mica powder 10-15% Modifier 5-9% The rest is polypropylene powder The modifier is obtained by blending N,N-ethylene bisstearic acid amide, polyvinyl alcohol and silicone masterbatch.
[0006] By adopting the above technical scheme, the ultra-high fluidity LCP composite material is prepared with low viscosity and good fluidity. The improved fluidity makes it easier for the LCP composite material to fill the mold during processing and easy to injection mold to form an ultra-thin product with uniform structure. At the same time, the LCP composite material also has high strength, high modulus, wear resistance, heat resistance, weather resistance and electrical properties.
[0007] Among them, polyethylene terephthalate has good fluidity and processing properties. Adding polyethylene terephthalate can reduce the overall viscosity of the composite material. At the same time, polyethylene terephthalate and LCP resin have good compatibility, which helps to form a uniform mixed system. Polyethylene has low viscosity and good fluidity. Its molecular chain is loose in the molten state, which can promote the flow of polyethylene terephthalate and LCP resin in the molten state, thereby improving the fluidity of the system.
[0008] Nano-scale mica powder, as an inorganic filler, not only enhances the mechanical properties of composite materials, but also improves processing performance through its nano effect. The high specific surface area and surface energy of nanoparticles help promote uniform dispersion and flow of materials. In addition, the interfacial interaction between nanoparticles and polymer matrix can also have a positive effect on the fluidity of LCP materials. Polypropylene powder is mainly used to adjust the overall performance and cost of composite materials. Its low viscosity and good processing performance also help improve the fluidity of composite materials.
[0009] 1. N-ethylene bisstearamide can form a lubricating layer during material processing, reducing the friction and resistance of the melt flow, thereby improving the fluidity of the system; polyvinyl alcohol can promote the slip and flow of molecular chains by reducing the interaction force between polymer molecular chains; silicone can penetrate into the melt to form a lubricating network, further reducing the friction and viscosity of the system melt. The combined use of the three can improve the processing fluidity of LCP composite materials and reduce the difficulty of processing.
[0010] Preferably, the weight ratio of the N,N-ethylene bisstearamide, the polyvinyl alcohol and the silicone masterbatch is (10-15):(5-9):3.
[0011] By adopting the above technical scheme, the dosage of N,N-ethylene bisstearamide, polyvinyl alcohol and silicone masterbatch is optimized, and the mixing of the raw materials in LCP is promoted, the melt viscosity of the LCP composite material can be significantly reduced, thereby improving its fluidity. At the same time, it helps to reduce the friction and wear of the LCP composite material during the processing, reduce the processing temperature and pressure, and thus improve the processing stability.
[0012] Preferably, the molecular weight of the polyvinyl alcohol is 2000-8000.
[0013] By adopting the above technical solution, the molecular weight of polyvinyl alcohol is optimized, which helps to reduce the melt viscosity of LCP and thus improve its fluidity; if the molecular weight of polyvinyl alcohol is too high, it may form physical cross-linking points, restricting the movement of LCP chain segments and thus reducing its fluidity; if the molecular weight of polyvinyl alcohol is small, it has little effect on the fluidity of LCP.
[0014] Preferably, the polypropylene powder is homopolypropylene, and the melt index at 230°C / 2.16Kg is 30-40g / 10min.
[0015] By adopting the above technical solution and optimizing the type and melt index of homopolypropylene, the high-fluidity polypropylene powder can flow and fill the mold more easily during processing, thereby reducing the processing temperature and injection pressure.
[0016] Preferably, the polyethylene is obtained by mixing polyethylene with a molecular weight of 5000-20000, polyethylene with a molecular weight of 20000-80000 and polyethylene with a molecular weight of 80000-200000 in a weight ratio of (10-12):(3-6):1.
[0017] By adopting the above technical solution, due to the high proportion of low molecular weight components in the mixed polyethylene, the fluidity of the composite material will be significantly improved, making it easier to fill the mold during processing, reducing processing temperature and pressure, and shortening the molding cycle. The low molecular weight component helps to improve fluidity, but the low molecular weight polyethylene will cause the mechanical properties of the LCP composite material to decrease. The presence of the high molecular weight component can compensate for the decrease in mechanical properties caused by the low molecular weight polyethylene, such as the loss of strength, rigidity and modulus.
[0018] Preferably, the polyethylene terephthalate has a melt index of 3-10 g / 10 min at 285° C. / 2.16 kg.
[0019] By adopting the above technical solution, the fluidity of LCP composite materials can be improved, making it easier for the composite materials to flow and fill the mold during processing. At the same time, under an appropriate melt index, the arrangement and entanglement of PET molecular chains may reach a balance point, thereby ensuring fluidity while maintaining good stability, reducing processing problems caused by material degradation or viscosity changes, and allowing LCP composite materials to maintain good mechanical properties.
[0020] Preferably, the average particle size of the nano-scale mica powder is 5-30 nm.
[0021] By adopting the above technical solution, the average particle size of the mica powder is optimized, so that the mica powder is more evenly dispersed in the LCP system, forming a denser microstructure, which helps to reduce the friction and resistance inside the material, thereby improving the fluidity of the LCP composite material, so that the high-fluidity LCP composite material can fill the mold more quickly during the injection molding process, reducing the phenomenon of glue shortage and incomplete filling.
[0022] Preferably, the nano-scale mica powder is modified nano-scale mica powder, which is prepared by the following method: The mica powder is heated at 200-300° C. for 1-2 hours, cooled, ethanol is mixed with the cooled mica powder, a thiol coupling agent is added, the mixture is heated and stirred, filtered, and dried to obtain a modified nano-scale mica powder; The weight ratio of the mica powder to the mercaptosilane coupling agent is 10:(1-1.5); The mercaptosilane coupling agent is -mercaptopropyltriethoxysilane and / or γ-mercaptopropyltrimethoxysilane.
[0023] By adopting the above technical solution, the dispersibility of nano-scale mica powder is improved, which helps to reduce the friction and resistance of LCP composite materials during processing, thereby improving its fluidity. Among them, the surface energy of mica powder after heat treatment increases, and the mixing with ethanol and thiol coupling agent is more uniform, so that the dispersibility of nano-scale mica powder in LCP system is significantly improved, which helps to reduce agglomeration and form a more uniform microstructure. At the same time, the thiol coupling agent can form a chemical bond with the surface of mica powder and LCP system, thereby enhancing the interfacial bonding force between the two, which helps to effectively transfer the load and improve the overall mechanical properties of the composite material.
[0024] In a second aspect, the present application provides a method for preparing an ultra-high fluidity LCP composite material, using the following technical solution: A method for preparing an ultra-high fluidity LCP composite material comprises the following preparation steps: S1, mixing LCP resin, polyethylene terephthalate, polyethylene, polypropylene powder, a modifier and nano-grade mica powder to obtain a mixture; S2. Melt and extrude the mixture through a twin-screw extruder, and granulate to obtain an ultra-high fluidity LCP composite material.
[0025] By adopting the above technical solution, various raw materials can be fully mixed, ensuring that the materials are fully melted, evenly mixed and maintain good fluidity during processing, thereby improving the overall performance and processing efficiency of the composite material. It is helpful to produce ultra-high fluidity LCP composite materials with higher quality and more stable performance to meet the wide application needs in the fields of electronics, aerospace, automobile manufacturing, etc.
[0026] Preferably, the process conditions of the twin-screw extruder are: zone one temperature 240-250°C, zone two temperature 250-270°C, zone three temperature 270-290°C, zone four temperature 270-290°C, zone five temperature 250-270°C, zone six temperature 250-270°C, zone seven temperature 240-250°C, zone eight temperature 230-250°C, zone nine temperature 230-250°C, zone ten temperature 230-250°C, die head temperature 290-310°C, and the residence time of the mixture is 35-40s.
[0027] By adopting the above technical solution, the process conditions of the twin-screw extruder are optimized so that the raw materials can be fully compatible and mixed, ensuring that the LCP composite material is fully plasticized during the extrusion process, thereby improving the fluidity and processing performance of the material. At the same time, avoiding excessively high temperatures can reduce the degradation of the material during the processing process and maintain the original performance of the material. Too long a residence time may cause the material to degrade or deteriorate at high temperatures, while too short a residence time may not allow the material to be fully melted and mixed.
[0028] In summary, this application has the following beneficial effects: 1. The present application adopts LCP resin, polyethylene terephthalate, polyethylene, nano-mica powder, modifier and polypropylene powder, wherein the modifier is obtained by blending N,N-ethylene bisstearamide, polyvinyl alcohol and silicone masterbatch. The above formula is used in combination to significantly reduce the viscosity of LCP and improve its fluidity, making the LCP composite material easier to process and shape, while also ensuring the strength, modulus and weather resistance of the PCL composite material. DETAILED DESCRIPTION Example
[0029] The liquid crystal polymer used was Sumitomo's E5002L, and the melt index was 123 g / 10 min at 285°C / 2.16 kg.
[0030] Polyethylene terephthalate is of the DuPont brand from the United States.
[0031] Polyethylene is from the United States Ticona.
[0032] All polypropylene uses Formosa Plastics brand from Taiwan, China.
[0033] The brand of silicone masterbatch is DuPont, and the model is MULTIBASE TM MB50-002.
[0034] Example 1 An ultra-high fluidity LCP composite material is prepared by the following preparation method: S1, 400g of LCP resin, 150g of polyethylene terephthalate, 130g of polyethylene, 80g of polypropylene powder, 90g of modifier and 150g of nano-grade mica powder were mixed to obtain a mixture; S2. Melt and extrude the mixture through a twin-screw extruder, and granulate to obtain an ultra-high fluidity LCP composite material.
[0035] The modifier is obtained by blending N,N-ethylenebisstearamide, polyvinyl alcohol and silicone masterbatch in a weight ratio of 10:5:3.
[0036] The molecular weight of polyvinyl alcohol is 2,000.
[0037] The melt index of polyethylene terephthalate at 285°C / 2.16Kg is 3g / 10min.
[0038] The molecular weight of polyethylene is 5000.
[0039] The polypropylene powder is polypropylene, and the melting index at 230°C / 2.16Kg is 6g / 10min.
[0040] The average particle size of nano-mica powder is 5nm.
[0041] Among them, the process conditions of the twin-screw extruder are: zone 1 temperature 240°C, zone 2 temperature 250°C, zone 3 temperature 270°C, zone 4 temperature 270°C, zone 5 temperature 250°C, zone 6 temperature 250°C, zone 7 temperature 240°C, zone 8 temperature 230°C, zone 9 temperature 230°C, zone 10 temperature 230°C, die head temperature 290°C, and the mixture residence time is 35s.
[0042] The difference between Example 2-3 and Example 1 is that the types, amounts and experimental parameters of some raw materials for preparing the ultra-high fluidity LCP composite material are different. The specific differences are shown in Table 1: Table 1 Examples 1-3 Preparation of ultra-high fluidity LCP composite materials Types, amounts and experimental parameters The molecular weight of polyvinyl alcohol in Example 2 is 5,000.
[0043] The molecular weight of polyvinyl alcohol in Example 3 is 8,000.
[0044] Example 4 A super-high fluidity LCP composite material, the difference between this embodiment and embodiment 1 is that the weight ratio of N,N-ethylene bisstearamide, polyvinyl alcohol and silicone masterbatch is 10:5:10.
[0045] Example 5 A super-high fluidity LCP composite material, the difference between this embodiment and embodiment 1 is that the weight ratio of N,N-ethylene bisstearamide, polyvinyl alcohol and silicone masterbatch is 3:5:3.
[0046] Example 6 An ultra-high fluidity LCP composite material, the difference between this embodiment and embodiment 1 is that the molecular weight of polyvinyl alcohol is 10000.
[0047] Example 7 An ultra-high fluidity LCP composite material, the difference between this embodiment and embodiment 1 is that the polyethylene is obtained by mixing polyethylene with a molecular weight of 5000, polyethylene with a molecular weight of 20000 and polyethylene with a molecular weight of 80000 in a weight ratio of 10:3:1.
[0048] Example 8 An ultra-high fluidity LCP composite material, the difference between this embodiment and embodiment 1 is that the polyethylene is obtained by mixing polyethylene with a molecular weight of 20,000, polyethylene with a molecular weight of 80,000 and polyethylene with a molecular weight of 200,000 in a weight ratio of 12:6:1.
[0049] Example 9 An ultra-high fluidity LCP composite material, the difference between this embodiment and embodiment 1 is that the polypropylene powder is random polypropylene powder, the melt index under the condition of 230°C / 2.16Kg is 30g / 10min, the brand is American INEOS, and the grade is PP240-CA12.
[0050] Example 10 An ultra-high fluidity LCP composite material, the difference between this embodiment and embodiment 1 is that the melt index of polyethylene terephthalate at 285° C. / 2.16 kg is 15 / 10 min.
[0051] Embodiment 11 An ultra-high fluidity LCP composite material, the difference between this embodiment and embodiment 1 is that the nano-scale mica powder is modified nano-scale mica powder, which is prepared by the following method: Heat 150 g of mica powder at 200° C. for 1 h, cool, mix 200 ml of ethanol with the cooled mica powder, add 15 g of a thiol coupling agent, heat and stir, filter, and dry to obtain modified nano-scale mica powder; The weight ratio of mica powder to mercaptosilane coupling agent is 10:1; The mercaptosilane coupling agent is mercaptopropyltriethoxysilane.
[0052] Example 12 An ultra-high fluidity LCP composite material, the difference between this embodiment and embodiment 1 is that the nano-scale mica powder is modified nano-scale mica powder, which is prepared by the following method: Heat 150 g of mica powder at 300° C. for 2 h, cool, mix 200 ml of ethanol with the cooled mica powder, add 22.5 g of a thiol coupling agent, heat and stir, filter, and dry to obtain modified nano-scale mica powder; The weight ratio of mica powder to mercaptosilane coupling agent is 10:1.5; The mercaptosilane coupling agent is 15 g of -mercaptopropyltriethoxysilane and 7.5 g of γ-mercaptopropyltrimethoxysilane.
[0053] Comparative Example Comparative Example 1 A high-fluidity LCP composite material, the difference between this comparative example and Example 1 is that stearic acid is used instead of the modifier.
[0054] Comparative Example 2 A high-fluidity LCP composite material, the difference between this comparative example and Example 1 is that stearic acid amide is used instead of N,N-ethylene bisstearic acid amide.
[0055] Comparative Example 3 A high-fluidity LCP composite material, the difference between this comparative example and Example 1 is that polyethylene wax is used instead of polyvinyl alcohol.
[0056] Comparative Example 4 A high-fluidity LCP composite material, the difference between this comparative example and Example 1 is that polydimethylsiloxane is used instead of silicone masterbatch.
[0057] The polydimethylsiloxane was from Dow Corning, USA, and had a viscosity of 1000 mPa.s at 25°C.
[0058] Comparative Example 5 A high-fluidity LCP composite material, the difference between this comparative example and Example 1 is that polycarbonate is used instead of polyethylene terephthalate.
[0059] The melt index of polycarbonate at 285°C / 2.16Kg is 3g / 10min, and the brand is Bayer from Germany.
[0060] Comparative Example 6 A high-fluidity LCP composite material, the difference between this comparative example and Example 1 is that polylactic acid is used instead of polyethylene.
[0061] The molecular weight of polylactic acid is 5,000.
[0062] Comparative Example 7 A high-fluidity LCP composite material, the difference between this comparative example and Example 1 is that polylactic acid is used instead of polypropylene powder.
[0063] The melt index of polylactic acid at 230°C / 2.16Kg is 6g / 10min, and the brand is American NatureWorks.
[0064] Performance testing The high-fluidity LCP composite materials prepared in Examples 1-12 and Comparative Examples 1-7 were subjected to melting point, viscosity, appearance observation and strength tests.
[0065] Detection method / test method Melting point of polymer: Differential scanning calorimetry (DSC) was used to measure the melting point of the above liquid crystal polymer. The temperature was raised from room temperature to 380°C at a heating rate of 10°C / min to melt the above polymer, and then the temperature was lowered to 30°C at a rate of 10°C / min, and then the temperature was raised to 380°C at a rate of 10°C / min. In the first cycle and the second cycle, the temperatures of the endothermic peaks were T1 and T2, respectively, and the average value T3 of T1 and T2 was taken as the melting point.
[0066] Viscosity measurement: at 1000s -1 The viscosity (Pa.s) of the polymer when it is above about 20°C from the melting point is measured with a viscometer at a shear rate of .
[0067] Appearance observation: Heat the polymer to a melting point of 30°C or above, and prepare a 5mm×5mm×0.1mm plastic film sheet by injection molding. Observe whether there are concave spots on the surface. If there are concave spots, do not perform strength test.
[0068] Strength test: Heat the polymer to a temperature above 30°C and prepare a 100mm×10mm×2mm plastic film by injection molding. Test the tensile strength according to ISO527 and the Izod notched impact strength according to ISO180 (KJ.m -2 ), tested 5 times respectively, and calculated the average value. The experimental data are shown in Table 2: Table 2 Experimental data of Examples 1-12 and Comparative Examples 1-7 Comparing Example 1 with Comparative Examples 1-4, the melt indexes of Comparative Examples 1-4 are 103 g / 10min, 88 g / 10min, 64 g / 10min and 76 g / 10min, respectively, and the melt index in Example 1 is 12 g / 10min; in the appearance test, pits appeared in Comparative Examples 1, 2 and 4; in the strength test, the tensile strength and Izod notch impact strength of Comparative Example 3 are lower than those of Example 1, indicating that in the present application, by blending N, N-ethylene bisstearamide, polyvinyl alcohol and silicone masterbatch to prepare a modifier, the melt index of LCP resin can be effectively reduced, the fluidity of LCP composite material can be increased, and at the same time, the LCP composite material maintains good physical and mechanical properties.
[0069] Comparing Example 1 with Comparative Examples 5-7, the melt indexes of Comparative Examples 5-7 are 41 g / 10 min, 32 g / 10 min and 38 g / 10 min, respectively; in the strength test, the tensile strength and Izod notched impact strength of Comparative Examples 6-7 are lower than those of Example 1, indicating that by using polypropylene, polyethylene and ethylene terephthalate to prepare LCP composite materials, the melt index of LCP resin can be effectively reduced, the fluidity of LCP composite materials can be increased, and at the same time, the LCP composite materials can maintain good physical and mechanical properties.
[0070] Comparing Example 1 with Example 4-5, the melt index of Example 4-5 is 21g / 10min and 23g / 10min, respectively; in the strength test, the tensile strength and the notched cantilever beam impact strength of Example 4-5 are lower than those of Example 1, indicating that the present application can effectively reduce the melt index of LCP resin, increase the fluidity of LCP composite material, and improve the physical and mechanical properties of LCP composite material by optimizing the dosage of N,N-ethylene bisstearamide, polyvinyl alcohol and silicone masterbatch.
[0071] Comparing Example 1 with Example 6, the melt index of Example 6 is higher than that of Example 1; in the strength test, the tensile strength and the notched cantilever beam impact strength of Example 6 are lower than those of Example 1, indicating that by optimizing the molecular weight of polyvinyl alcohol, the melt index of the LCP resin can be further reduced, the fluidity of the LCP composite material can be increased, and the physical and mechanical properties of the LCP composite material can be improved.
[0072] Comparing Example 1 with Example 7-8, the melt index of Example 7-8 is lower than that of Example 1; in the strength test, the tensile strength and Izod notch impact strength of Example 7-8 are higher than those of Example 1, indicating that optimizing the type of ethylene is beneficial to reducing the melt index of LCP resin, increasing the fluidity of LCP composite materials, and improving the physical and mechanical properties of LCP composite materials.
[0073] Comparing Example 1 with Example 9-10, the melt index of Example 9-10 is higher than that of Example 1; in the strength test, the tensile strength and the notched cantilever beam impact strength of Example 9-10 are lower than those of Example 1, indicating that by optimizing the melt index of polypropylene and ethylene terephthalate, it is beneficial to reduce the melt index of LCP resin, increase the fluidity of LCP composite material, and improve the physical and mechanical properties of LCP composite material.
[0074] Comparing Example 1 with Example 11-12, the melt index of Example 11-12 is lower than that of Example 1. In the strength test, the tensile strength and the notched cantilever beam impact strength of Examples 11-12 are higher than those of Example 1, indicating that the modified nano-mica powder prepared in the present application can further reduce the melt index of the LCP resin, increase the fluidity of the LCP composite material, and improve the physical and mechanical properties of the LCP composite material.
[0075] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An ultra-high fluidity LCP composite material, characterized in that: Prepared from the following raw materials in weight percentage: LCP resin 40-50% Polyethylene terephthalate 10-15% Polyethylene 9-13% Nano-grade mica powder 10-15% Modifier 5-9% The rest is polypropylene powder The modifier is obtained by blending N,N-ethylene bisstearic acid amide, polyvinyl alcohol and silicone masterbatch.
2. The ultra-high fluidity LCP composite material according to claim 1, characterized in that: The weight ratio of the N,N-ethylene bisstearamide, the polyvinyl alcohol and the silicone masterbatch is (10-15): (5-9):
3.
3. The ultra-high fluidity LCP composite material according to claim 1, characterized in that: The polypropylene powder is homopolypropylene, and the melting index under the condition of 230° C. / 2.16 kg is 30-40 g / 10 min.
4. The ultra-high fluidity LCP composite material according to claim 1, characterized in that: The molecular weight of the polyvinyl alcohol is 2000-8000.
5. The ultra-high fluidity LCP composite material according to claim 1, characterized in that: The polyethylene is obtained by mixing polyethylene with a molecular weight of 5000-20000, polyethylene with a molecular weight of 20000-80000 and polyethylene with a molecular weight of 80000-200000 in a weight ratio of (10-12): (3-6):
1.
6. The ultra-high fluidity LCP composite material according to claim 1, characterized in that: The polyethylene terephthalate has a melting index of 3-10 g / 10 min at 285° C. / 2.16 kg.
7. The ultra-high fluidity LCP composite material according to claim 1, characterized in that: The average particle size of the nano-scale mica powder is 5-30 nm.
8. The ultra-high fluidity LCP composite material according to claim 7, characterized in that: The nano-scale mica powder is modified nano-scale mica powder, which is prepared by the following method: The mica powder is heated at 200-300° C. for 1-2 hours, cooled, ethanol is mixed with the cooled mica powder, a thiol coupling agent is added, the mixture is heated and stirred, filtered, and dried to obtain a modified nano-scale mica powder; The weight ratio of the mica powder to the mercaptosilane coupling agent is 10:(1-1.5); The mercaptosilane coupling agent is -mercaptopropyltriethoxysilane and / or γ-mercaptopropyltrimethoxysilane.
9. A method for preparing the ultra-high fluidity LCP composite material according to any one of claims 1 to 8, characterized in that: The method comprises the following preparation steps: S1, mixing LCP resin, polyethylene terephthalate, polyethylene, polypropylene powder, a modifier and nano-grade mica powder to obtain a mixture; S2. Melt and extrude the mixture through a twin-screw extruder, and granulate to obtain an ultra-high fluidity LCP composite material.
10. The method for preparing an ultra-high fluidity LCP composite material according to claim 9, characterized in that: The process conditions of the twin-screw extruder are: temperature of zone 1 is 240-250°C, temperature of zone 2 is 250-270°C, temperature of zone 3 is 270-290°C, temperature of zone 4 is 270-290°C, temperature of zone 5 is 250-270°C, temperature of zone 6 is 250-270°C, temperature of zone 7 is 240-250°C, temperature of zone 8 is 230-250°C, temperature of zone 9 is 230-250°C, temperature of zone 10 is 230-250°C, temperature of die head is 290-310°C, and residence time of the mixture is 35-40s.